Treatment of Subclinical Hypothyroidism; A Review of Literature - Asad Ali Mughal, Syed Taha Abbas, Huma Asad, Muhammed Zubair, Ramsha Mujeeb, Nasir Ali Khan, Shehla Naseem, Muhammad Zaman Shaikh, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Subclinical hypothyroidism (SCH) is a disorder without any symptoms related with an elevated thyroid stimulating hormone (TSH) concentration > 4 mIU/l and normal T4 and T3 concentrations. It is communal in the elderly and particularly in females, with prevalence of about 11%. Some studies show no effect of the treatment, while others have found it to be beneficial, since normal TSH levels can be above 7.5 mIU/L in the elderly. As a result of these findings, the best treatment for SCH, especially in elderly patients, has been criticized. Aim: The aim of this study was to evaluate the latest literature on the subject in order to assess the available evidence regarding this controversy in order to determine whether and under what conditions treatment of SCH is essential and how it can be prevented. Methods: To better understand the ongoing debate regarding the treatment of SCH, a Medline search of the English-language literature was held between 2015 and 2022 using the terms subclinical hypothyroidism, hypothyroidism, treatment and prevention, cardiovascular disease, dyslipidemia and cardiac failure. From this search, 38 articles with relevant material were selected. Results: When the data from these studies were combined, it was found that normal TSH levels increased with age, from 4 to 7.5 mIU/L in subjects under 75 years of age. Levothyroxine supplementation has also shown marked effects on the metabolic and clinical features of SCH, including decline in cardiovascular disease, heart failure, and mortality, although many of the peer-reviewed articles exhibited no treatment benefit. The drug works best in younger people who also experience fewer side effects. Conclusions: Younger patients with TSH > 4.0 mIU/l should be treated for SCH based on available data. Treatment must be modified according to the TSH levels and existence of symptoms, and should be started with a TSH level of 10 mIU/L with moderate doses to minimize adversative cardiovascular complications in elderly patients. Keywords: subclinical, discussion, thyroxine, treatment, hypothyroidism, hypertension, thyrotropin, dyslipidemia, heart failure, cardiovascular diseases, prevention.